Semiotic Analysis and Visual Narrative in Eric Carle’s The Very Hungry Caterpillar - Najwa Khoerunnisa Muflihin; Otong Setiawan Djuharie (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study explores how Eric Carle’s children’s storybook The Very Hungry Caterpillar creates depth in its narrative through visual components and tactile elements despite its limited text. Using a multimodal analysis approach, this study highlights the texture of the collage, the use of symbolic colors, and the die-cut holes as elements that can be felt. The results of this study show that the physical design of this book is not merely decorative, but functions as a key narrative guide that helps children understand the concepts of growth and change independently. The die-cut holes have a specific role as a physical symbol of hunger, allowing young readers to interact directly with the story. The combination of the book’s materials and visual storytelling has proven to transcend language barriers, making it an effective literacy tool for beginner readers. This research confirms that visual storytelling intertwined with the physical form of a book can convey complex philosophical themes more effectively than narratives composed solely of dense text. The success of this book confirms that tactile and visual elements are important literary tools in the world of children’s literature.